Recent progress in migraine and cognitive disorder - Xiao-Wen, Song; Lin, Cao; Jin-Bo, Chen; Xin-Tong, Wu (International Journal of Research in Medical Sciences, 2017)
Migraine is a chronic neurovascular disease characterized by recurrent unilateral headache, which induces incapacity. At present, there are many methods to evaluate cognitive function, and the cognitive function scale is commonly used. Recently, event-related potentials, resting state functional magnetic resonance imaging and other new technologies have been widely used to assess the cognitive function of migraine patients because of their high temporal resolution and high spatial resolution. In this paper, we can overview that the research progress of the relationship between migraine and methods of evaluate cognitive function.